70 Impact of timing of cytoreductive surgery(CRS) on epithelial ovarian cancer(EOC), primary peritoneal carcinomatosis(PPC), and fallopian tube cancer(FTC) at american university of beirut medical center(AUBMC). (18th September 2019) - Seoud, M; El Housheimi, A; Jaafar, I; Hamed, K; Jamali, F; Abdallah, R; Khalil, A
Abstract : Objectives: To study the impact of timing of CRS weather done at diagnosis or following neoadjuvant chemotherapy(NACT) on progression free(PFS) and overall survival(OS) of patients with advanced EOC between 1997–2017 at AUBMC. Patients underwent either primary debulking (PDS) or received NACT followed by interval debulking surgery (IDS) in cases with extensive disease, multiple comorbidities, or poor performance status. Methods: A retrospective review of the impact of PDS versus NACT followed by IDS on PFS and OS. Results: Of 273 patients with EOC, PPC and FTC, 220 were found to have advanced epithelial cancer (stage IIIB, IIIC and IV). 63% had interval debulking surgery (IDS) while 37% had primary debulking (PDS). Results are shown in table 1 . In stage IIIC, the PFS of patients who underwent PDS was significantly higher than patients undergoing IDS (table 1, Pvalue=0.003). In Stage IV, the PFS was not significantly affected by the timing of surgery (table 1, Pvalue=0.274). The OS was not afffected by the timing of CRS in all stages. Conclusions: Timing of the CRS (PDS vs. IDS) significantly impacts PFS but not OS in stage IIIC but not IV EOC. This difference in survival is explained by the higher tumor burden, higher morbidity, and worse performance status of patients who underwent IDS.